Assessing Nursing Students’ Readiness for Clinical Practice: A Comprehensive Evaluation - Mohammed, Qahtan Qasim; Faraj, Taha Ahmed; Sachit, Kareem Rashag (Nurse Media Journal of Nursing, 2026)
Background: Nursing students’ clinical readiness is important for a smooth transition into practical settings; however, evidence on the level of readiness and the factors that influence it remains limited. Existing studies often provide only a partial understanding of preparedness, particularly regarding demographic and psychosocial characteristics.Purpose: This study aimed to assess the level of work readiness among fourth-year nursing students and to examine its association with selected demographic and psychosocial variables.Methods: A descriptive cross-sectional study was conducted across five purposively selected colleges of nursing in Iraq. The sample consisted of 550 final-year nursing students. Data were collected using a sociodemographic questionnaire and an 18-item work readiness scale. Descriptive and inferential statistics (chi-square tests) were used for data analysis.Results: Among the 550 nursing students, 62.7% were female, 94.5% were unmarried, and 48.2% perceived their socioeconomic status as middle. Work readiness was moderate in 57.3% of students, with a mean score of 52.43 (SD = 3.999). Significant associations were found between readiness and gender (p = .001), socioeconomic status (p = .001), educational level prior to college (p = .001), support system (p = .001), and interest in nursing (p = .001).Conclusion: The study found that students are moderately to well prepared for their nursing careers. They demonstrate the ability to think critically and provide care in clinical contexts, as reflected in their problem-solving skills. These findings highlight the need for targeted educational and psychosocial support strategies to further enhance students’ readiness for professional practice.